Marine Biofuels Costs and Emissions Study for the European Supply Chain Till 2030 - Gartland, Nicolas; Pruyn, Jeroen (Frontiers in Energy Research, 2022)
The design and preliminary estimations of biomass supply chains are essential in matching energy supply to energy demand. This is especially true of novel/future fuels and technologies in large industries. In this paper, a Mixed Integer Linear Programming (MILP) model was formulated to represent biofuel supply chains across Europe for the production of three novel marine fuels and to allow the selection of fuel conversion technologies, biomass supply locations, and the logistics of transportation from resources to conversion and from conversion to final markets. On top of this, the total production costs and emissions were calculated and compared to current marine fuels to assess the implementation potential and feasibility of these fuels. The MILP model was used to design and analyze optimal distribution and conversion systems, using a realistic data-set covering the European member states and 15 of the largest bunkering ports in the EU. The results showed that on average, the fuels obtained a 72% greenhouse gas (GHG) reduction compared to a fossil fuel comparator and ranged from 22–36 €/GJ in total production costs. It was also discovered that forestry residues were the best-suited biomass for the production of these fuels and that Poland had the highest supply potential of all considered states. The available supply of biomass was sufficient for the demand in the foreseeable future, the largest impediment to the adoption of these fuels is the available refining potential in Europe.